2003
DOI: 10.1016/s0960-9822(03)00547-5
|View full text |Cite
|
Sign up to set email alerts
|

The Minus End-Directed Motor Kar3 Is Required for Coupling Dynamic Microtubule Plus Ends to the Cortical Shmoo Tip in Budding Yeast

Abstract: The budding yeast shmoo tip is a model system for analyzing mechanisms coupling force production to microtubule plus-end polymerization/depolymerization. Dynamic plus ends of astral microtubules interact with the shmoo tip in mating yeast cells, positioning nuclei for karyogamy. We have used live-cell imaging of GFP fusions to identify proteins that couple dynamic microtubule plus ends to the shmoo tip. We find that Kar3p, a minus end-directed kinesin motor protein, is required, whereas the other cytoplasmic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 23 publications
7
82
1
Order By: Relevance
“…The similar kinetochore distribution pattern in cik1 HU and cin8 mutants raises the possibility that the Cik1/Kar3 complex also plays a role in chromosome congression. Indeed, the Cik1/Kar3 complex binds to the end of the microtubule and promotes its depolymerization (Maddox et al 2003;Sproul et al 2005). However, we found that cin8 mutants are not sensitive to HU.…”
Section: Discussioncontrasting
confidence: 44%
“…The similar kinetochore distribution pattern in cik1 HU and cin8 mutants raises the possibility that the Cik1/Kar3 complex also plays a role in chromosome congression. Indeed, the Cik1/Kar3 complex binds to the end of the microtubule and promotes its depolymerization (Maddox et al 2003;Sproul et al 2005). However, we found that cin8 mutants are not sensitive to HU.…”
Section: Discussioncontrasting
confidence: 44%
“…Additionally, NCD, which shares 42.2% amino acid sequence identity to ATK5 inside the motor domain was identified as an interacting partner with the ϩTIP EB1 in Drosophila S2 cells (Rogers et al, 2004). A fusion between Kar3p and GFP has been shown to localize to plus-ends of astral microtubules in the budding yeast schmoo tip, although in this case the enrichment was greater during microtubule depolymerization (Maddox et al, 2003). Further advances in microscopic imaging and GFP technology may reveal additional Kinesin-14 family members with ϩTIP activity.…”
Section: Minus-end Motors and Plus-end Trackingmentioning
confidence: 99%
“…However, KAR3 when expressed dimerizes with either Cik1 or Vik1, both non-nucleotide binding proteins, to generate two functionally distinct kinesin-14 motors in vivo (3)(4)(5)(6). Kar3Cik1 during mating promotes MT 2 shortening for karyogamy, the nuclear fusion event (3)(4)(5)(6)(7)(8)(9)(10). In contrast, during mitosis Kar3Cik1 cross-links anti-parallel ipMTs (11), and its inward force stabilizes the spindle by counter-balancing the outward forces generated by kinesin-5 Cin8 and Kip1 (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%